# Solve for s 2(s+2)-2=7(s+1)-5s 2(s+2)-2=7(s+1)-5s
Since s is on the right side of the equation, switch the sides so it is on the left side of the equation.
7(s+1)-5s=2(s+2)-2
Simplify 7(s+1)-5s.
Simplify each term.
Apply the distributive property.
7s+7⋅1-5s=2(s+2)-2
Multiply 7 by 1.
7s+7-5s=2(s+2)-2
7s+7-5s=2(s+2)-2
Subtract 5s from 7s.
2s+7=2(s+2)-2
2s+7=2(s+2)-2
Simplify 2(s+2)-2.
Simplify each term.
Apply the distributive property.
2s+7=2s+2⋅2-2
Multiply 2 by 2.
2s+7=2s+4-2
2s+7=2s+4-2
Subtract 2 from 4.
2s+7=2s+2
2s+7=2s+2
Move all terms containing s to the left side of the equation.
Subtract 2s from both sides of the equation.
2s+7-2s=2
Combine the opposite terms in 2s+7-2s.
Subtract 2s from 2s.
0+7=2
Add 0 and 7.
7=2
7=2
7=2
Since 7≠2, there are no solutions.
No solution
Solve for s 2(s+2)-2=7(s+1)-5s

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top